PENGGUNAAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERLIBATAN SISWA DALAM MENGGUNAKAN BAHASA INGGRIS DI SMA SUNAN DRAJAT SUGIO - Hasyim, Nur (MEDIA DIDAKTIKA, 2022)
Audio-Visual Learning Model in fact can improve student learning and achievement activities.The data collection method is observation and learning achievement tests. Data analysis methods is descriptive is good for qualitative data as well as for quantitative data.Remaining barriers that need to be discussed is the learning achievements achieved in cycle I have yet to meet expectations in accordance with the demands of the KKM United Kingdom Language subjects at this school namely 7.5 therefore attempts further improvements still need to be strived so need to do planning more ripe for the next cycle.Of the value gained students, more students got half the value of 8.5, 13 students earn intermediate value that is 8.From a comparison of this value can already believed that the achievements of the student learning can be enhanced with the use of Audio-Visual method.See a comparison of the initial value, the value of the cycle I and cycle II values, there was a significant rise, from an average initial value is 4.5 rise in cycle I became 6.3 and in cycle II rose to 7.9 this Increase could not be considered one eye because This value is the increment of the maximal efforts implemented researchers for the sake of educational enhancement and advancement of education especially at the HIGH SCHOOL of Sunan Drajat Sugio.The conclusions derived from this study was the audio-visual learning models can improve learning achievement.